Pengaturan Fungsi Badan Kependudukan dan Keluarga Berencana Nasional Dalam Mengendalikan Laju Pertumbuhan Penduduk - Reynaldi Don Reto; Kotan Y. Stefanus; Rafael Rape Tupen (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
Population growth in Kupang Regency from year to year is increasing, based on the population census data of Kupang Regency the number of residents by gender (soul), the population of Kupang Regency amounted to 372, 777 people with details of 190, 480 people for men and 182, 297 people for women. The density problem that occurred was 63 people per km2. High population growth can be a serious problem if it is not solved immediately, the high and uncontrolled population growth rate will affect the declining level of welfare of the community and family. . The family planning program began in 1968 by preparing LKBN (national family planning institution) which later became the National Population and Family Planning Agency or BKKBN, the national family planning movement aims to control the rate of population growth and also improve the quality of human resources. This research is a normative judicial research supported by an approach that uses primary data and secondary data obtained using interview methods, documentation studies and observations and the data obtained is processed using editing, coding, induction, trigulation and tabulation methods and analyzed in a qualitative descriptive manner. The results of this study show that (1) Regulation regarding the function of the district government in population control by BKKBN in Kupang Regency. In the hierarchy of legislative arrangements from the highest to the lowest level, it gives very full authority or trust to the National Population and Family Planning Agency in controlling the rate of population growth in Kupang Regency (2) In carrying out the functions of the population and family planning agency in organizing population control in Kupang Regency. The Population and Family Planning Agency has provided services and education to the public about the importance of family planning. However, the function of BKKBN has not been running well, this can happen because of the lack of public awareness, socio-cultural constraints, limited access to counter-septic tools, patriarchal gender roles, religious keyness and economic factors that make the function of BKKBN not well in controlling the population in Kupang Regency.